Design, preparation method and application of polarized white organic light-emitting diode

By introducing a distributed Bragg reflector structure into the organic light emitting diodes, the Fabry-Perot resonance cavity is formed, which solves the challenges of single-emitting layer white-light organic light emitting diodes in terms of efficiency and color control, and achieves low angle-dependent white light luminescence and high external quantum efficiency.

CN119584776AActive Publication Date: 2025-03-07BEIJING UNIV OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411701474.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Single-emitting layer white-light organic light emitting diodes have challenges in improving efficiency and controlling color, and their polarization modulation and response times are long.

Method used

By introducing a distributed Bragg reflector structure into the organic light emitting diode, a Fabry-Perot resonance cavity is formed, and the device microcavity length is adjusted to achieve resonance between the exciton and the cavity membrane, resulting in strongly coupled polaron emission.

Benefits of technology

Low or angle-free white light emission is achieved, external quantum efficiency reaches 4.52%, rabic splitting energy is as high as 511meV, divergence angle is reduced from 70° to 50°, and white light is at all angles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005153420970000011
    Figure HDA0005153420970000011
  • Figure HDA0005153420970000012
    Figure HDA0005153420970000012
  • Figure HDA0005153420970000021
    Figure HDA0005153420970000021
Patent Text Reader

Abstract

The invention discloses a design, preparation method and application of a polarized white-light organic light-emitting diode, and belongs to the field of diodes. The distributed Bragg reflector is integrated into the green organic light-emitting diode, the distributed Bragg reflector and a metal aluminum electrode of the organic light-emitting diode form a Fabry-Perot resonant cavity, light emitting of the organic light-emitting diode is modulated, and exciton and cavity membrane resonance formed by a light-emitting material is achieved by adjusting the cavity length of a device microcavity. Strong coupling is generated, polaron emission is formed, and light emission is changed into polaron white light emission from green light emission. Single-peak green light of a single light-emitting layer is converted into double-peak white light, the distributed Bragg reflector has high reflectivity in a forbidden band region of the distributed Bragg reflector, the quality of a Fabry-Perot resonant cavity formed by the distributed Bragg reflector and an aluminum electrode is guaranteed, the forbidden band position is controlled to be a proper position by controlling the film thickness of each layer of the distributed Bragg reflector, and the light emitting efficiency is improved. Strong coupling polaron white light emission is further realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the design, preparation method and application of a polarized white light organic light emitting diode, belonging to the technical field of organic light emitting diodes. Background Art

[0002] White light-emitting organic light-emitting diodes are becoming a key technology for the next generation of energy-efficient solid-state lighting and full-color flat-panel displays. Much effort has been devoted to the exploration of functional materials, the manipulation and distribution of excitons, the optimization of device configurations, and the development of manufacturing technologies. In general, the reported material design approaches can be divided into two main methods. The first involves vertically or horizontally stacking emission layers to produce white light by mixing the light emitted independently by red, green, and blue organic light-emitting diodes. While these strategies lead to stable white emission, achieving the desired color balance is complicated by the need to precisely control the thickness and composition of each layer. The second approach involves constructing a single emission layer that is fabricated by combining a matrix material and multiple doped emitters. White light can be generated by either Dexter energy transfer or by bimolecular excited species such as excimers and exciplexes.

[0003] Compared with the first strategy, single-emission layer white light-emitting organic diodes are favored for commercialization due to their greatly simplified device structure and reduced production cost. However, the major challenge lies in the rational control of singlet and triplet excitons within the single emission layer, making the simultaneous improvement of efficiency and control of color a fundamental issue for single-emission layer white light-emitting organic diodes. Another approach to achieve white light-emitting organic diodes is to reconstruct the spectrum by introducing optical resonances. Typical optical resonators include plasmon resonators, Mie resonators, Fabry-Perot cavities, quantum crystal cavities, and hybrid cavities, which can generate strong light fields to enhance the interaction of light with matter, represent the building blocks of modern optoelectronics, and lead to the realization of many transformative optical devices with desired functionalities. The introduction of these resonators is a promising strategy to address challenges such as poor full-color tunability, limited polarization modulation, and long response time. In particular, when the light-matter interaction between the electromagnetic modes of the cavity and the electronic excitations enters the strong regime, new half-light, half-matter bosonic quasiparticles, called exciton-polaritons, are often generated, becoming a very important control over the coherent, delocalized properties of polariton energy levels and polaritons. The corresponding OLED devices are called polaritonic OLEDs.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a design, preparation method and application of a polarized white light organic light emitting diode to achieve a highly efficient white light organic light emitting diode with low or no angle dependence (white light at different emission angles).

[0006] First, the light-emitting layer is tested to obtain its photoluminescence spectrum and electroluminescence spectrum to further determine the exciton energy.

[0007] According to the Helmholtz equation, it can be deduced that when the material in the microcavity is determined, whether the cavity film and exciton can resonate is only related to the cavity length. The resonance range of the cavity length is determined by the derived formula, and then the organic light-emitting diode is optimized to determine the optimal cavity length for its optical and electrical performance. The optimization of optical performance is optimized by simulation calculation and adjusting the thickness of the electron transport layer. Because the refractive index of the electron transport layer is relatively large, the impact on the optical performance is more significant than other layers, such as the hole transport layer. The optimal range of optical performance is obtained when the strongest field intensity distribution inside the device is at the light-emitting layer. The optimization of electrical performance is to calculate the thickness range when the injection equilibrium is reached through the carrier mobility of the material used, and the optimal cavity length, that is, the thickness of each layer of film, is obtained by comprehensive consideration. The cavity length refers to the sum of all dielectric films contained in the resonant cavity composed of the distributed Bragg reflector and the metal cathode of the organic light-emitting diode.

[0008] The polarized white light organic light emitting diode of the present invention is characterized in that a distributed Bragg reflector is deposited on a glass substrate, a tungsten-doped indium oxide anode film is disposed on the distributed Bragg reflector, a hole injection layer PEDOT:PSS is disposed on the tungsten-doped indium oxide anode film, a light-emitting layer is disposed on the hole injection layer PEDOT:PSS, and a hole blocking layer, an electron transport layer, a modified transition layer and a metal cathode electrode layer are disposed on the light-emitting layer in sequence.

[0009] The distributed Bragg reflector selects a high refractive index material of tantalum pentoxide and a low refractive index material of silicon dioxide to be alternately stacked. The thickness of the tantalum pentoxide layer is the same, which is 56-60nm; the thickness of the silicon dioxide layer is the same, which is 81-85nm.

[0010] The thickness of the tungsten-doped indium oxide anode film is 180 nanometers; the thickness of the hole injection layer PEDOT:PSS film is 30 nanometers. The luminescent layer is composed of polyvinyl carbazole and the main and guest materials of the luminescent layer, and the main material and the guest material of the luminescent layer are CBD and BD-F respectively. The mass ratio of polyvinyl carbazole and the main and guest materials of the luminescent layer is 1:3:1, and the thickness of the luminescent layer film is 30 nanometers. The thicknesses of the hole blocking layer, the electron transport layer, the modification layer and the aluminum electrode layer are 10 / 70 / 1 / 130 nanometers respectively.

[0011] The preparation method of the polarized white light organic light emitting diode of the present invention is as follows:

[0012] Step 1: Deposit a distributed Bragg reflector on the prepared glass substrate by electron beam evaporation equipment. The distributed Bragg reflector selects a high refractive index material of tantalum pentoxide and a low refractive index material of silicon dioxide to be alternately stacked.

[0013] Step 2: Place the substrate obtained in step 1 into a vacuum thermal evaporation device to deposit the anode thin film of tungsten-doped indium oxide.

[0014] Step 3: Drop-coat a hole injection layer PEDOT:PSS on the substrate obtained in step 2, perform annealing, and cool to room temperature.

[0015] Step 4: Accurately weigh polyvinyl carbazole and the host and guest materials of the light-emitting layer according to a certain ratio, put them into a glass bottle and transfer them into a glove box, add a certain amount of solvent chlorobenzene to dissolve them in the glove box, and place them on a heating table to heat.

[0016] Step 5: The substrate obtained in step 3 is transferred into a glove box, and the solution obtained in step 4 is spin-coated, annealed, and then cooled to room temperature.

[0017] Step 6: A plurality of polarized white light organic light emitting diode arrays can be prepared at one time, and the light emitting layer around each polarized white light organic light emitting diode is removed to expose the corresponding anode;

[0018] Step 7: After the light-emitting layer is prepared, it is transferred to a vacuum thermal evaporation device to sequentially evaporate a hole blocking layer, an electron transport layer, a modified transition layer and a metal cathode electrode layer to obtain a polarized white light organic light-emitting diode.

[0019] In step 1 of the above invention, the glass substrate is first immersed in deionized water with detergent added, and the surface of the glass substrate is wiped with cotton using tweezers, followed by ultrasonication twice using deionized water, acetone and ethanol, each for 20 minutes. -4 The evaporation was carried out under Pa conditions, and the evaporation rate was controlled at The silicon dioxide layer in the distributed Bragg reflector has the same thickness, the tantalum pentoxide layer has the same thickness, and the silicon dioxide layer and the tantalum pentoxide layer have different thicknesses.

[0020] In the above invention, in step 2, when vacuum thermal evaporation is used, the vacuum degree is less than 3*10 -4 The evaporation was carried out under Pa conditions, and the evaporation rate was controlled at About, the thickness is controlled at 180 nanometers.

[0021] In the above invention content, in step 3, the doping ratio of polyvinyl carbazole and the host and guest materials of the light-emitting layer is 1 mg: 3 mg: 1 mg, the volume of the solvent chlorobenzene is 0.5 ml, and the heating time on the heating table is more than 6 hours at a temperature of 60°C.

[0022] In step 4 of the above invention, the coating speed is 2900 rpm and the time is 40 seconds. After the coating is completed, annealing is performed for 15 minutes at a temperature of 160°C. After annealing, the substrate is quickly transferred to a glove box and cooled to room temperature before subsequent operations. The film thickness is 30 nanometers.

[0023] In step 5 of the above invention, the light-emitting layer is prepared by spin coating at 3000 rpm for 60 seconds. After the spin coating, annealing is performed for 30 minutes at 60° C. The film thickness is 30 nanometers.

[0024] In step 6 of the above invention, a scraper is used to remove the film around each polarized white light organic light emitting diode to the anode position, so that each polarized white light organic light emitting diode corresponds to an independent anode film.

[0025] In step 7 of the above invention, when vacuum thermal evaporation is used, evaporation is performed under the condition of vacuum degree lower than 3*10-4Pa, and the evaporation rate is controlled at The thicknesses of the hole blocking layer, electron transport layer, modification layer and aluminum electrode layer are 10 / 70 / 1 / 130 nanometers, respectively.

[0026] The present invention integrates a distributed Bragg reflector into an organic light-emitting diode, and the distributed Bragg reflector and the metal aluminum electrode of the organic light-emitting diode form a Fabry-Perot cavity to modulate the light emission of the organic light-emitting diode. By adjusting the length of the device microcavity, the exciton formed by the light-emitting material and the cavity film resonate, resulting in strong coupling, forming polariton emission, so that the light emission changes from green light emission to polariton white light emission. In the present invention, through the realization of strong coupling, the single-peak green light of a single light-emitting layer is converted into double-peak white light, wherein the designed distributed Bragg reflector has a high reflectivity in its bandgap region, ensuring the quality of the Fabry-Perot cavity formed by it and the aluminum electrode, and by controlling the film thickness of each layer of the distributed Bragg reflector, the bandgap position is controlled at a suitable position, further realizing strong coupling polariton white light emission.

[0027] The present invention integrates a distributed Bragg reflector into a green organic light-emitting diode, generates strong coupling, forms polaron emission, and converts a single-light-emitting layer green organic light-emitting diode into a polarized white organic light-emitting diode. The obtained polarized white organic light-emitting diode has an external quantum efficiency of 4.52% for the best performance device, a Rabi splitting energy of up to 511 meV, generates polaron emission, and reduces the divergence angle from 70° to 50°. It is white light at all angles and has low angle dependence. The prepared polarized white organic light-emitting diode has certain application prospects in the fields of display and lighting. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0029] Figure 1 , is a schematic diagram of the structure of a green organic light emitting diode and a polarized white organic light emitting diode;

[0030] Figure 2 , is a schematic diagram of the distributed Bragg reflector structure.

[0031] Figure 3 , is the image of the tungsten-doped indium oxide substrate under atomic force microscopy. RMS characterizes the surface roughness;

[0032] Figure 4 , is the image of the distributed Bragg reflector and the tungsten-doped indium oxide substrate under atomic force microscopy. RMS characterizes the surface roughness;

[0033] Figure 5 , is a comparison chart of the experimental results and simulation calculation results of the reflectivity of the distributed Bragg reflector and the tungsten-doped indium oxide substrate.

[0034] Figure 6 , is the positive emission spectrum of green light organic light emitting diode and polarized white light organic light emitting diode.

[0035] Figure 7 , is the external quantum efficiency-brightness curve of green organic light emitting diode and polarized white organic light emitting diode

[0036] Figure 8 , are the color coordinates of green organic light emitting diodes and polarized white organic light emitting diodes and the corresponding physical images. (The color coordinates are calculated through the spectrum)

[0037] Fig. 9 , are the electroluminescence spectra and the corresponding color coordinates of Experimental Example 1 at different emission angles.

[0038] (0° is positive emission) DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0040] Example 1

[0041] The prepared glass substrate was transferred to the electron beam evaporation equipment and the vacuum degree was 3*10 -4 Pa, the distributed Bragg reflector is deposited on the glass substrate. Tantalum pentoxide is first deposited on the glass substrate at a rate of After cooling, silicon dioxide is continuously deposited at a rate of Repeat the deposition until a distributed Bragg reflector with a period of 5 is formed. The total number of layers is 10, and the structure is an alternating thin film of tantalum pentoxide and silicon dioxide, each with 5 layers. The thickness of silicon dioxide and tantalum pentoxide is 85 / 60 nanometers respectively. After cooling to room temperature, take it out. Then put it into the vacuum thermal evaporation equipment and place it in a vacuum of 3*10 -4 Pa under the conditions of electrode tungsten-doped indium oxide deposition, the evaporation rate is

[0042] Use a ten-thousandth analytical balance to accurately weigh 1 mg of polyvinyl carbazole, 3 mg of the main material CBP, and 1 mg of the guest luminescent material BD-F and put them into the same glass bottle. Gently loosen the bottle mouth and transfer it into the glove box. Add 0.5 ml of chlorobenzene solution to dissolve it, and place the glass bottle on a heating table at 60°C for more than 6 hours. After it is fully dissolved, make a spin coating solution for the luminescent layer.

[0043] The PEDOT:PSS hole injection layer was drop-coated on the substrate with the distributed Bragg reflector and tungsten-doped indium oxide. After the drop-coating, it was annealed at 160°C for 15 minutes. After completion, it was immediately transferred to the glove box and cooled to room temperature. The light-emitting layer was prepared by the solution method. 26 microliters of solution were taken and spin-coated at a speed of 3000 rpm for 60 seconds. The substrate after film spinning was annealed at 60°C for 30 minutes. After cooling to room temperature, a scraper was used to remove the thin film prepared by the solution method at the position where the anode was covered, and then transferred to the evaporation chamber. The vacuum degree was 3*10 -4Pa, the hole blocking layer (DPEPO), electron transport layer (TmPyPb), modification layer (LiF) and cathode electrode aluminum layer were sequentially deposited. The evaporation rate of organic materials was controlled at The LiF evaporation rate is controlled at The electrode aluminum evaporation rate is controlled at about.

[0044] Example 2

[0045] The prepared glass substrate was transferred to the electron beam evaporation equipment and the vacuum degree was 3*10 -4 Pa, the distributed Bragg reflector is deposited on the glass substrate. Tantalum pentoxide is first deposited on the glass substrate at a rate of After cooling, silicon dioxide is continuously deposited at a rate of Repeat the deposition until a distributed Bragg reflector with a period of 5 is formed. The total number of layers is 10. The structure is an alternating thin film of tantalum pentoxide and silicon dioxide, each with 5 layers. The thickness of silicon dioxide and tantalum pentoxide is 81 / 56 nanometers respectively. After cooling to room temperature, take it out. Then put it into the vacuum thermal evaporation equipment and place it in a vacuum of 3*10 -4 Pa under the conditions of electrode tungsten-doped indium oxide deposition, the evaporation rate is

[0046] Use a ten-thousandth analytical balance to accurately weigh 1 mg of polyvinyl carbazole, 3 mg of the main material CBP, and 1 mg of the guest luminescent material BD-F and put them into the same glass bottle. Gently loosen the bottle mouth and transfer it into the glove box. Add 0.5 ml of chlorobenzene solution to dissolve it, and place the glass bottle on a heating table at 60°C for more than 6 hours. After it is fully dissolved, make a spin coating solution for the luminescent layer.

[0047] The PEDOT:PSS hole injection layer was drop-coated on the substrate with the distributed Bragg reflector and tungsten-doped indium oxide. After the drop-coating, it was annealed at 160°C for 15 minutes. After completion, it was immediately transferred to the glove box and cooled to room temperature. The light-emitting layer was prepared by the solution method. 26 microliters of solution were taken and spin-coated at a speed of 3000 rpm for 60 seconds. The substrate after film spinning was annealed at 60°C for 30 minutes. After cooling to room temperature, a scraper was used to remove the thin film prepared by the solution method at the position where the anode was covered, and then transferred to the evaporation chamber. The vacuum degree was 3*10 -4 Pa, the hole blocking layer (DPEPO), electron transport layer (TmPyPb), modification layer (LiF) and cathode electrode aluminum layer were sequentially deposited. The organic material evaporation rate was controlled at The LiF evaporation rate is controlled at The electrode aluminum evaporation rate is controlled at about.

[0048] By introducing a distributed Bragg reflector structure into an organic light-emitting diode, a single-layer green organic light-emitting diode is converted into a polarized white organic light-emitting diode. The optimized cavity length is calculated to achieve strong coupling, forming polaron emission. The divergence angle is reduced from 70° to 50°, and the turn-on voltage is reduced from 5.0V to 4.6V. The Rabi splitting energy is calculated to be as high as 511meV, confirming the generation of strong coupling and polaron emission. The positive emission spectra of green organic light-emitting diodes and polarized white organic light-emitting diodes are tested, and the corresponding color coordinates are calculated and the device physical diagram is given, which more intuitively shows the conversion of green light emission into polarized white light emission. By testing the emission spectrum of polarized white organic light-emitting diodes at different angles and calculating the corresponding color coordinates, the corresponding color coordinates are within the white light range at all emission angles, achieving white light at all angles. The device performance of green organic light-emitting diodes and polarized white organic light-emitting diodes, that is, the curve of external quantum efficiency and device brightness, is tested, and a polarized white organic light-emitting diode with an external quantum efficiency of up to 4.52% is obtained.

[0049] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A polarized white light organic light emitting diode, characterized in that: A distributed Bragg reflector is deposited on a glass substrate, on the distributed Bragg reflector is a tungsten-doped indium oxide anode film, on the tungsten-doped indium oxide anode film is a hole injection layer PEDOT:PSS, on the hole injection layer PEDOT:PSS is a light-emitting layer, on the light-emitting layer are a hole blocking layer, an electron transport layer, a modified transition layer and a metal cathode electrode layer in sequence.

2. A polarized white light organic light emitting diode according to claim 1, characterized in that: The distributed Bragg reflector selects tantalum pentoxide, a high refractive index material, and silicon dioxide, a low refractive index material, to be alternately stacked; the thickness of the tantalum pentoxide layer is the same, which is 56-60nm; the thickness of the silicon dioxide layer is the same, which is 81-85nm.

3. A polarized white light organic light emitting diode according to claim 1, characterized in that: The distributed Bragg reflector is composed of tantalum pentoxide and silicon dioxide, a low refractive index material, which are alternately stacked in five cycles.

4. A polarized white light organic light emitting diode according to claim 1, characterized in that: The thickness of the tungsten-doped indium oxide anode film is 180 nanometers; the thickness of the hole injection layer PEDOT:PSS film is 30 nanometers; the light-emitting layer is composed of polyvinyl carbazole and the main and guest materials of the light-emitting layer, and the main material and the guest material of the light-emitting layer are CBD and BD-F respectively; the mass ratio of polyvinyl carbazole and the main and guest materials of the light-emitting layer is 1:3:1, and the thickness of the light-emitting layer film is 30 nanometers; the thicknesses of the hole blocking layer, the electron transport layer, the modification layer and the aluminum electrode layer are 10, 70, 1 and 130 nanometers respectively.

5. The polarized white light organic light emitting diode according to claim 1, characterized in that: The single-peak green light of a single luminous layer is converted into double-peak white light. The designed distributed Bragg reflector has a high reflectivity in its bandgap region, ensuring the quality of the Fabry-Perot cavity formed with the aluminum electrode. By controlling the film thickness of each layer of the distributed Bragg reflector, the bandgap position is controlled at a suitable position, further realizing strongly coupled polariton white light emission.

6. A polarized white light organic light emitting diode according to claim 1, characterized in that: The resulting polarized white light organic light-emitting diode has an external quantum efficiency of 4.52% for the best performance device, a Rabi splitting energy of up to 511 meV, white light at all angles, and low angle dependence.

7. The method for preparing a polarized white light organic light emitting diode according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Depositing a distributed Bragg reflector on a prepared glass substrate by electron beam evaporation equipment, wherein the distributed Bragg reflector is composed of tantalum pentoxide, a high refractive index material, and silicon dioxide, a low refractive index material, alternately stacked; Step 2: placing the substrate obtained in step 1 into a vacuum thermal evaporation device to deposit anode thin film tungsten-doped indium oxide; Step 3: drop-coating a hole injection layer PEDOT:PSS on the substrate obtained in step 2, performing annealing treatment, and cooling to room temperature; Step 4: accurately weigh polyvinyl carbazole and the host and guest materials of the light-emitting layer according to a certain ratio, put them into a glass bottle and transfer them into a glove box, add a certain amount of solvent chlorobenzene to dissolve them in the glove box, and place them on a heating table for heating; Step 5: transfer the substrate obtained in step 3 into a glove box, spin-coat the solution obtained in step 4, anneal, and then cool to room temperature; Step 6: A plurality of polarized white light organic light emitting diode arrays can be prepared at one time, and the light emitting layer around each polarized white light organic light emitting diode is removed to expose the corresponding anode; Step 7: After the light-emitting layer is prepared, it is transferred to a vacuum thermal evaporation device to sequentially evaporate a hole blocking layer, an electron transport layer, a modified transition layer and a metal cathode electrode layer to obtain a polarized white light organic light-emitting diode.

8. The method according to claim 7, characterized in that In step 1, the glass substrate is first immersed in deionized water with detergent added, and the surface of the glass substrate is wiped with cotton using tweezers, followed by ultrasonication twice with deionized water, acetone, and ethanol, each for 20 minutes. -4 The evaporation was carried out under Pa conditions, and the evaporation rate was controlled at The silicon dioxide layer in the distributed Bragg reflector has the same thickness, the tantalum pentoxide layer has the same thickness, and the silicon dioxide layer and the tantalum pentoxide layer have different thicknesses.

9. The method according to claim 7, characterized in that In step 2, when vacuum thermal evaporation is used, the vacuum degree is less than 3*10 -4 The evaporation was carried out under Pa conditions, and the evaporation rate was controlled at about; In step 3, the coating speed is 2900 rpm and the time is 40 seconds. After the coating is completed, annealing is performed for 15 minutes at a temperature of 160° C. After the annealing is completed, the substrate is quickly transferred to a glove box and cooled to room temperature. In step 4, the doping ratio of polyvinyl carbazole and the host and guest materials of the light-emitting layer is 1 mg: 3 mg: 1 mg, and the volume of the solvent chlorobenzene corresponding to each polyvinyl carbazole is 0.5 ml; the heating time on the heating table is more than 6 hours, and the temperature is 60° C.; In step 5, the light-emitting layer is prepared by spin coating, the spin coating speed is 3000 rpm, the time is 60 seconds, and annealing is performed after the spin coating, the annealing time is 30 minutes, and the annealing temperature is 60° C.; In step 6, a scraper is used to remove the film around each polarized white light organic light emitting diode to the anode position, so that each polarized white light organic light emitting diode corresponds to an independent anode film; In step 7, when vacuum thermal evaporation is used, the vacuum degree is less than 3*10 -4 The evaporation was carried out under Pa conditions, and the evaporation rate was controlled at And it is not 0, and the hole blocking layer, electron transport layer, modification layer and aluminum electrode layer are evaporated respectively.

10. Application of the polarized white light organic light emitting diode according to any one of claims 1 to 6 in display and lighting applications.

Citation Information

Patent Citations

  • White light OLED device and display device

    CN108987609A

  • Organic light-emitting device

    CN111602258A

  • Application of thermally active delayed fluorescent material capable of being processed in solution in blue light devices and hybrid white light devices

    CN113078278A

  • Preparation method and application of hole transport layer containing functionalized nickel oxide, trans-perovskite solar cell and preparation method of trans-perovskite solar cell

    CN117979781A

  • Organic white light emitting diode in tiny cavity type

    CN1728413A